Staff Operational Guidance on The Dissemination of Capacity Development Information. - International Monetary Fund. Institute for Capacity Development (Washington, D.C. : International Monetary Fund, 2022)
The Staff Operational Guidance on Dissemination of Capacity Development Information sets forth procedures on the dissemination of capacity development information, based on the objectives of wider, more active, and timelier sharing of information while safeguarding the Fund's candor and role as trusted advisor. The guidance draws from internal consultations and Executive Directors' views on the Updated Framework on the Dissemination of Capacity Development Information.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Monetary Policy; Money and Monetary Policy; Political Economy